EVALUASI PELAKSANAAN PILKADA SERENTAK TAHUN 2015 - Hasrul Harahap (Jurnal Renaissance, 2016)
The election simultaneously 2015 still triggered several problems. This research intend to evaluate the election simultaneously the first wave of 2015 year and conduct an analysis of several a clause in the revision number 8 years 2015 about the local election to be performed by the parliament with the government. This research in a qualitative approach descriptive analytical, that explains, visualizing and analyze the process of the election simultaneously 2015. The research obtained data as follows First , with the data purification of voters is one of the activities to be held simultaneously election a very complex and crucial and directly influence the other phases of the election .Second , their level of participation of voters in the next local election simultaneously 2015 in general are still low. Based on general election commission (KPU), participation voters only about 64, 23 percent, or lower than the commission about 75,5 percent. Third, to support “simultaneously” the regional election, need to the principle of election simultaneously based on spirit efficiency and the effectiveness. Fourth, In the revision of the local election, need to be added arrangement on; a prohibition for incumbent to do replacement officials and ban on the and activities local government for the elections; security participation a political party contesting 2014 in the election simultaneously as a manifestation of rules the constitution article 18 paragraph (4) 1945 constitution; and security issues unity that election simultaneously next not caused horizontal conflicts broad.Key words: Evaluation the regional election simultaneously 2015; the revision of the local election; Participation voters of the local election